Beneficial effects of fluvastatin following percutaneous coronary intervention in patients with unstable and stable angina: results from the Lescol intervention prevention study (LIPS). Issue 10 (14th September 2004) - Lee, C H; de Feyter, P; Serruys, P W; Saia, F; Lemos, P A; Goedhart, D; Soares, P R; Umans, V A W M; Ciccone, M; Cortellaro, M
Abstract : Aims: To investigate the effect on risk of major adverse cardiac events (MACE) of lipid lowering treatment with fluvastatin 80 mg/day after a first percutaneous coronary intervention in patients with stable and unstable angina. Method and results: This prespecified subgroup analysis of the LIPS (Lescol intervention prevention study) analysed 1658 patients with documented diagnosis; 824 had unstable angina (417 randomly assigned to fluvastatin, 407 to placebo) and 834 had stable angina (including silent ischaemia; fluvastatin, 418; placebo, 416). Median follow up was 3.9 years. There was no significant effect of anginal status on long term risk of MACE. Fluvastatin treatment reduced the risk of MACE by 28% compared with placebo (p  =  0.03) among patients with unstable angina, with no difference between patients with stable and patients with unstable angina (relative risk 1.07, 95% confidence interval 0.87 to 1.30, p  =  0.53). Fluvastatin reduced coronary atherosclerotic events (MACE excluding restenosis) by 36% (p  =  0.006) among patients with unstable angina and 31% (p  =  0.02) among patients with stable angina. Fluvastatin caused similar reductions in total cholesterol and low density lipoprotein cholesterol concentrations in both patient groups. Conclusion: Treatment with fluvastatin 80 mg/day produced significant reductions in MACE and coronary atherosclerotic events after percutaneous coronary intervention in patients with average cholesterol concentrations. The beneficial effects of fluvastatin are observed in patients with unstable or stable angina alike.